2019
DOI: 10.1016/j.tcr.2019.100214
|View full text |Cite
|
Sign up to set email alerts
|

A novel fixation method for panfacial fracture using an Ilizarov-type external fixator

Abstract: In general, internal plate fixation is mainly performed in order to reduce multiple facial bone fractures and rarely uses an external fixator. Although it would be ideal to successfully achieve or preserve the occlusal relationship of the upper and lower jaws, it is difficult to successfully manage multiple bone fragments in order to use them to achieve internal fixation, especially when treating a severely comminuted facial fracture. In addition, it is also important to prevent the onset of severe infection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…Hihara et al showed similar insertion site selection in their case study published in 2019. In particular, the pins in the hard palate were placed in the same location [ 8 ]. The alternative is to insert one pin in the zygomatic bone on each side.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hihara et al showed similar insertion site selection in their case study published in 2019. In particular, the pins in the hard palate were placed in the same location [ 8 ]. The alternative is to insert one pin in the zygomatic bone on each side.…”
Section: Discussionmentioning
confidence: 99%
“…The use of an Ilizarov-type external fixator for CMF was first described in a case report by Hirara et al in 2019. This type of fixation was chosen as an alternative to plate osteosynthesis due to an uncontrollable intraoral bleeding caused by a severe panfacial fracture of a 70-year-old woman [ 8 ]. In high-income countries (HIC) these factures are treated with mini-plates, even in extensive comminuted fractures [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1). Furthermore there are different approaches for exposure and fixation based on experience of the surgeon (8). Some surgeons considered reconstruction of occlusion as the first step in treatment and begin with mandible.…”
Section: Discussionmentioning
confidence: 99%
“…It was applied for traumatic skull defects and brain vascularity stimulation after brain stroke but the techniques remained on the stage of uncompleted clinical trials. On the contrary, the role and significance of craniomaxillofacial distraction procedures have been much discussed in the specialized literature and has been found applicable in craniofacial deficiency or dentofacial anomalies that are corrected with distraction procedures and special devices[ 132 , 133 ]. Another Ilizarov’s idea of stimulating the vascularity in chronic ischemic diseases in the lower extremities has been revived and its modification has been called tibial transverse distraction[ 134 , 135 ].…”
Section: Current Clinical Practice and Research In The Ilizarov Techniques Of Bone Reconstructionmentioning
confidence: 99%